2018
DOI: 10.1108/jedt-09-2017-0088
|View full text |Cite
|
Sign up to set email alerts
|

Design for safety implementation factors: a literature review

Abstract: Purpose: Decisions made during the design stage of construction works can significantly reduce the risk of occurrence of occupational accidents, injuries and illnesses. Moreover it has been established that design is one of the major contributors of accidents and injuries. Design for safety (DfS) studies within construction have highlighted factors affecting the implementation of DfS, amongst which are: designer attitude; DfS knowledge/awareness and education; availability of DfS tools including guidance; clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 27 publications
(58 reference statements)
1
39
0
2
Order By: Relevance
“…level of performance. Recent studies (for instance, Goh and Chua, 2016;Poghosyan et al, 2018) have also indicated that clients and end-users provide the greatest motivation for undertaking PtD in the construction industry. Unfortunately, clients are usually indicted for their weak support for PtD on construction projects (Oney-Yazici and Dulaimi, 2014;Hwang et al, 2014).…”
Section: Prevention Through Design (Ptd) Philosophy In Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…level of performance. Recent studies (for instance, Goh and Chua, 2016;Poghosyan et al, 2018) have also indicated that clients and end-users provide the greatest motivation for undertaking PtD in the construction industry. Unfortunately, clients are usually indicted for their weak support for PtD on construction projects (Oney-Yazici and Dulaimi, 2014;Hwang et al, 2014).…”
Section: Prevention Through Design (Ptd) Philosophy In Constructionmentioning
confidence: 99%
“…This philosophy places a moral, as well as in some jurisdictions a legal, duty on designers to originate designs or construction products that are inherently safe for construction, occupation, maintenance and demolition. Some researchers (for example, Gambatese et al 2005, López-Arquillos et al 2015, Goh and Chua 2016, Poghosyan et al 2018 The nexus between procurement as well as design decisions and OSH risks downstream of the project development process came to the attention of the European Union (EU) and its European Council (EC) responded by adopting Council Directive 1992/57/EEC on the implementation of minimum safety and health requirements at temporary or mobile construction sites. This Directive requires the appointment of two types of coordinators for health and safety matters on construction projects that will require more than one contractor on the construction site.…”
mentioning
confidence: 99%
“…Analisis struktur poros pada desain barrier gate dilakukan untuk memastikan kemampuan poros yang menahan beban palang [4]. Perhitungan dari kekuatan struktur poros berkaitan dengan faktor keamanan dari desain barrier gate [5].…”
Section: Pendahuluanunclassified
“…Karena terdapat kombinasi antara momen bending dan momen puntir pada poros maka dilakukan kalkulasi terhadap maximum shear stress theory atau guest's theory [4] bahwa besarnya tekanan geser maksimun dapat dijabarkan oleh persamaan berikut:…”
Section: Perhitungan Terhadap Kekuatan Poros Barrier Gateunclassified
“…One of the prominent initiatives to address the poor status of OSH is design for occupational safety and health (DfOSH), also known as "prevention through design", "design for safety, and "safety in design". While there is a growing body of research on DfOSH in construction (see Poghosyan et al, 2018), empirical work on DfOSH capability of design firms (or more broadly organisations with design responsibility) is sparse (Manu et al, 2017).This study thus examines DfOSH capability. In particular it presents the development of a capability maturity model for DfOSH.…”
Section: Introductionmentioning
confidence: 99%